Research on vertical air leakage law of surface in goaf of shallow coal seams under different seasonal conditions - ZHU Xingpan; WANG Yang; REN Xiaowei; YAN Li; ZHANG Linjiang; LIU Wenyong; JIN Yongfei; CHEN Yuliang (Gong-kuang zidonghua, 2023)
Under the influence of mining, the overlying strata of shallow coal seam fully mechanized top coal caving face collapses and forms cracks that connect with the surface. The vertical air leakage caused by these cracks has a significant impact on the spontaneous combustion of coal in the goaf. In order to study the vertical air leakage law of surface in goaf of shallow coal seam under different seasonal conditions, SF6 gas tracing method is used to measure the vertical air leakage on the 122108 working face of Shaanxi Coal Caojiatan Mining Co., Ltd. in four seasons: winter, spring, summer, and autumn. The temperature, atmospheric pressure, and air leakage rate changes on the surface and underground goaf during different seasons are analyzed. The results show the following points. ① In winter, the temperature difference between the surface of the working face and the underground goaf is relatively large, with a maximum temperature difference of 37.7 ℃. In summer, the temperature difference between the surface of the working face and the underground goaf is relatively small, with a minimum temperature difference of only 0.9 ℃. The maximum pressure difference between the surface of the working face and the underground goaf in winter is 40.37 hPa. The maximum pressure difference between the surface of the working face and the underground goaf in summer is 22.47 hPa. The temperature difference and pressure difference between the surface and underground goaf of the working face in spring and autumn are not significantly different. ② The winter air leakage rate is relatively high, with an average maximum air leakage rate of 8.364 m/min. The air leakage rate in summer is relatively small, with an average maximum air leakage rate of 6.918 m/min. The air leakage rates in spring and autumn are not significantly different. ③ When close to the working face, the air leakage rate is relatively high. According to the vertical air leakage law on the surface, measures such as underground pressure equalization, sealing of inlet and outlet air corners, and surface crack coverage can be taken to ensure the safe mining of 122108 working face.